ANALISIS PENENTUAN TARIF BIAYA SATUAN PENDIDIKAN DENGAN MENGGUNAKAN METODE ACTIVITY BASED COSTING DI MAN 1 BAGANSIAPIAPI KABUPATEN ROKAN HILIR - Nur aini, Nur aini; Gusnardi, Gusnardi; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to find out the exact cost of education based on calculation the method activity based costing in MAN 1 Bagansiapiapi, Rokan Hilir district. Data collection method used is documentation study. Based on the results of the stady it is know that the charging of education unit costs by using the ABC, method is obtained by the cost of education unit fees at MAN 1 Bagansiapiapi. The total education unit cost of class X is Rp 66.517 per month, the total education unit cost of class XI is Rp 74.666 per month, and the total education unit cost of class XII is Rp 69.437 per month. The determination of these rates is calculated using committee funds. Calculation of education unit costs using the ABC method can maximize the costs incurred by students each month. While the unit cost of education applied by the school user tradisional system methods so far the exactwa education unit costs is Rp 75.000 per month.Keywords : Education Cost, Activity Based Costing